2014
DOI: 10.1002/ejic.201400119
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic Three‐Dimensional Molecular Conductor Based on the Coronene Radical Cation

Abstract: In this study, we obtained the first cation radical solid of a highly symmetric (D6h) polyaromatic hydrocarbon, coronene, by electrooxidation. The (coronene)3Mo6Cl14 salt, which is formed with an Oh‐symmetric molybdenum cluster unit Mo6Cl142–, has an isotropic cubic structure with Pm$\bar {3}$m symmetry. The presence of two orientations for the coronene molecules related by an in‐plane 90° rotation (merohedral disorder) allows for fourfold symmetry along the <100> direction. The disorder has dynamic features b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…Previously, we reported that the Raman‐active A 1g mode is sensitive to the charge state of coronene molecules, and, therefore, the splitting of the band observed for (coronene) 3 Mo 6 Cl 14 ( 3 ) is indicative of charge disproportionation (Figure ; see Figure S3 in the Supporting Information for spectra over a wider range) . In contrast, the A 1g band at 1373 cm −1 for 2 is well‐fitted by a single Lorentzian function, which strongly indicates uniform charge on A and B .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Previously, we reported that the Raman‐active A 1g mode is sensitive to the charge state of coronene molecules, and, therefore, the splitting of the band observed for (coronene) 3 Mo 6 Cl 14 ( 3 ) is indicative of charge disproportionation (Figure ; see Figure S3 in the Supporting Information for spectra over a wider range) . In contrast, the A 1g band at 1373 cm −1 for 2 is well‐fitted by a single Lorentzian function, which strongly indicates uniform charge on A and B .…”
Section: Resultsmentioning
confidence: 74%
“…To date, structurally refined coronene anion salts formed with Na(dimethoxyethane) 3 + , K(tetrahydrofuran) 2 ( N , N , N ′, N ′‐tetramethylethylenediamine) +[29] and Rb(18‐crown‐6) +[30] have been obtained by alkali‐metal doping in solution, in which the coronene molecules coordinate to the alkali‐metal ions or ligands instead of assembling into π columns. On the other hand, our group recently reported the first coronene cation salts, (coronene) 3 Mo 6 X 14 (X=Cl, Br), obtained by the electro‐oxidation of coronene in the presence of molybdenum halide cluster dianions (Mo 6 X 14 2− ) in solution . However, the salts have a three‐dimensional (3D) anti‐perovskite structure, in which there are no face‐to‐face π–π interactions between adjacent cationic coronene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that investigation of the arrangement patterns of electron-donating/accepting rotator molecules suitable for reducing the rotational barrier would encourage the rational design of CT-type supramolecular rotors. [1][2][3][4][13][14][15][16][17][18][19]36,39 In particular, the present results strongly suggest the possibility of controlling dynamic properties over a wide range by intermolecular interactions. By extrapolating the Arrhenius law to higher temperatures, it is likely that the molecular rotation of coronene in 2 should occur with a frequency as high as ca.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…300 MHz for slower species and ca. 2.6 GHz for faster species at 233 K), 36 were found to be one of the fastest rotators in the coronene-based CT complexes with alternating columns. This confirms the importance of molecular arrangement or intermolecular interactions, i.e., C−H···N and C−H···F hydrogen bonds with adjacent F 4 TCNQ molecules along the side-byside direction and π−π interactions with adjacent coronene and F 4 TCNQ molecules along the stacking direction, in determining dynamic properties.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…[1][2][3][4] Beyond carrying specific luminescence, sensitization, catalytic and photo-catalytic properties, they could be involved in the material structuration by self-assembling of organic cationic frameworks [5] in charge transfer salts thanks to their ability to form hydrogen bonding. Indeed, many molecular assemblies and nanomaterials built up from M 6 clusters carriers of original chemical and physical properties [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] or as structuring moieties have been reported these last years.…”
Section: Introductionmentioning
confidence: 99%